2008
DOI: 10.1007/s12272-008-1118-5
|View full text |Cite
|
Sign up to set email alerts
|

Antiulcerogenic activity of fractions and 3,15-Dioxo-21α-hydroxy friedelane isolated from Maytenus robusta (Celastraceae)

Abstract: The hexane, chloroform, ethyl acetate and aqueous-soluble fractions from leaves of Maytenus robusta (Celastraceae) were evaluated for their protective actions against ethanol-induced gastric lesions in rats. The treatment with all fractions (150 mg/kg) and omeprazol (30 mg/kg) significantly reduced the lesion index, the total lesion area, and the percentage of lesion, in comparison with the control group (p<0.05). Since the ethyl acetate-soluble fraction was found to be most active in the pylorus ligated model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 24 publications
1
19
0
2
Order By: Relevance
“…These compounds possess pharmacological properties exhibiting antiinflammatory (Fu et al 2005), antibacterial (Katerere et al 2003), antifungal (Yuan et al 2008), antiviral (Zhu et al 2001;Kuo et al 2009), antitumor (Saxena et al 2006;Kuo et al 2009), antidiabetic (Wen et al 2005), antiulcerogenic (De Andrade et al 2008), anticariogenic (Segal et al 2006), hepatoprotective (Liu 1995), neuroprotective (Lee and Kim 2001), antiparasitic (Danelli et al 2009), analgesic (Tapondjou et al 2003), antioxidant (D'Abrosca et al 2005) and other effects. The pharmacological activities of natural triterpenoids and their therapeutic implications have been reviewed (Dzubak et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…These compounds possess pharmacological properties exhibiting antiinflammatory (Fu et al 2005), antibacterial (Katerere et al 2003), antifungal (Yuan et al 2008), antiviral (Zhu et al 2001;Kuo et al 2009), antitumor (Saxena et al 2006;Kuo et al 2009), antidiabetic (Wen et al 2005), antiulcerogenic (De Andrade et al 2008), anticariogenic (Segal et al 2006), hepatoprotective (Liu 1995), neuroprotective (Lee and Kim 2001), antiparasitic (Danelli et al 2009), analgesic (Tapondjou et al 2003), antioxidant (D'Abrosca et al 2005) and other effects. The pharmacological activities of natural triterpenoids and their therapeutic implications have been reviewed (Dzubak et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A atividade antiulcerogênica de triterpenos pentaciclícos foi relatada por Andrade et al (2008). Uma análise estrutural e histoquímica das folhas de S. stipulaceum revelou a presença de terpenos no parênquima foliar, bem como pronunciado acúmulo destes compostos em quase todos os órgãos desta espécie, indicando uma maior diferença estrutural em relação a outras espécies do gênero (Matias et al, 2016).…”
Section: Resultsunclassified
“…Triterpene, as well as omeprazole, both at a dose of 30 mg/kg, significantly decreased all the parameters when compared to the control group (p < 0.05). Thus, the authors suggest that the antiulcer effect observed in the extract and fractions may be partly attributable to this compound [22].…”
Section: Maytenus Genusmentioning
confidence: 97%
“…Preparations obtained from the leaves of Maytenus ilicifolia are widely used in Brazil, where the plantis popularly known by different names, such as congorça, erva cancerosa, espinho-de-deus, quebrachillo, sombra-de-toro, concorosa, and finally the most commonly used name by the local population, "espinheira santa" or "espinheira." However, other species of this genus, such as Maytenus aquifolium, Maytenus Robusta, and Maytenus truncate, are also known by the same names and are also used in folk medicine to treat gastric disorders [19][20][21][22].…”
Section: Maytenus Genusmentioning
confidence: 99%